Pengaruh Motivasi, Beban Kerja, dan Penguasaan Teknologi Informasi terhadap Kinerja Karyawan - Farhan Fathia Andriawan; Sri Astuti Pratminingsih (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the effect of motivation, workload, and information technology mastery on employee performance at PT Terakorp Indonesia. The background of this research stems from the phenomenon of decreased work results, which is suspected to be caused by low motivation levels, high workload, and a lack of ability to master information technology in supporting employee work activities. This study employed a quantitative method with an associative approach. The population included all employees, with the sample determined using the Slovin formula and the purposive sampling technique. Data were collected through questionnaires and analyzed using the Statistical Package for the Social Sciences (SPSS) version 25 with multiple linear regression analysis. The results revealed that motivation, workload, and information technology mastery simultaneously have a significant effect on employee performance. Partially, motivation and information technology mastery have a significant effect on employee performance, while workload has no significant effect. These findings indicate that enhancing work motivation and information technology mastery, along with managing workload proportionally, can improve overall employee performance.